3D Printed Functional and Biological Materials on Moving Freeform Surfaces. Issue 23 (25th April 2018) - Zhu, Zhijie; Guo, Shuang‐Zhuang; Hirdler, Tessa; Eide, Cindy; Fan, Xiaoxiao; Tolar, Jakub; McAlpine, Michael C.
Abstract: Conventional 3D printing technologies typically rely on open‐loop, calibrate‐then‐print operation procedures. An alternative approach is adaptive 3D printing, which is a closed‐loop method that combines real‐time feedback control and direct ink writing of functional materials in order to fabricate devices on moving freeform surfaces. Here, it is demonstrated that the changes of states in the 3D printing workspace in terms of the geometries and motions of target surfaces can be perceived by an integrated robotic system aided by computer vision. A hybrid fabrication procedure combining 3D printing of electrical connects with automatic pick‐and‐placing of surface‐mounted electronic components yields functional electronic devices on a free‐moving human hand. Using this same approach, cell‐laden hydrogels are also printed on live mice, creating a model for future studies of wound‐healing diseases. This adaptive 3D printing method may lead to new forms of smart manufacturing technologies for directly printed wearable devices on the body and for advanced medical treatments. Abstract : An adaptive 3D printing system capable of printing functional conductive inks and bioinks on moving freeform surfaces yields wireless electronics on a moving human hand and cell‐laden biostructures on mice. The concept of printing functional and biological materials via an autonomous, adaptive 3D printing system suggests a new paradigm for printing on‐the‐fly wearable electronics on moving targets and for surgical applications.